An updated phylogeny of Deprea (Solanaceae) with a new species from Colombia: interspecific relationships, conservation assessment, and a key for Colombian species. Issue 7 (3rd October 2018) - Deanna, Rocío; Orejuela, Andrés; Barboza, Gloria Estela
Abstract : Deprea is a neotropical genus that comprises 51 species. Recent work based on molecular data has explored its monophyly and interspecific relationships, but the relationships amongst Deprea species were not entirely elucidated. The inclusion of more accessions and molecular markers in phylogenetic analysis is likely to produce more supported hypotheses. Therefore, the main objective of this study was to perform a combined phylogenetic analysis of Deprea including seven new samples representing six species and one more DNA plastid marker than in previous studies. In that process, a new species of Deprea from Colombia was discovered and is described and illustrated here. Deprea teresitae Deanna & A. Orejuela, sp. nov. is morphologically similar to D. dilloniana and phylogenetically closely related to D. hawkesii and D. harlingiana . This new species is distinguished by the combination of short calyx lobes, non-mucronate anthers, long staminal filaments and corolla lobes, and elongated appressed fruiting calyx around a subglobose green berry. The new phylogenetic results are presented, including discussion on phylogenetic interspecific relationships, taxonomy, geographic distribution, and conservation status from D. teresitae . The synonymy of Deprea sylvarum subsp. novogranatensis under D. glabra is also proposed and an identification key to the 10 Deprea species distributed in Colombia is included.